We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
129
1
avatar

first five terms for each expression:

 

a) 3n -1

 

b) 6n + 2

 Dec 17, 2018
 #1
avatar+103122 
+2

I'll do the first.....the second should be easy based on this

 

3(1) - 1  = 2

3(2) - 1  = 5

3(3) - 1  = 8

3(4) - 1 = 11

3(5) - 1  = 14

 

cool cool cool

 Dec 17, 2018

6 Online Users

avatar
avatar